High Technology in Medicine: Lessons from Cardiovascular Innovations and Future Perspective - Beyar, Rafael (Rambam Health Care Campus, 2013)
Four decades of innovations in the field of interventional cardiology are presented as an example for the great growth of high technology in medicine, side by side with the development of general technology and science. The field of percutaneous coronary intervention (PCI) was enabled by the development of X-ray systems, allowing us to view the pathology, and was critically dependent on courageous and imaginative physicians and scientists who developed percutaneous transluminal coronary angioplasty (PTCA), stents, and transarterial aortic valve replacement (TAVR). Today, outstanding research continues to progress, with stem cell research and IPC technologies presenting new challenges and yet taller mountains to climb. The rapid development we have witnessed was due to tight collaborations between clinical and academic institutions and industry. The combination of all these elements, with a proper mechanism to handle conflict of interest, is an essential linkage for any progress in this field. We will continue to see exponential growth of innovations and must be prepared with appropriate bodies to encourage such developments and to provide early-stage funding and support for novel ideas.